Expression of fragile X mental retardation protein and Fmr1 mRNA during folliculogenesis in the rat - Ferder, Ianina Claudia (2013)
Fragile X mental retardation protein (FMRP) belongs to a small family of RNA-binding proteins. Its absence or inactivity is responsible for fragile X syndrome, the most common cause of inherited mental retardation. Despite its ubiquitous expression, FMRP function and expression remain almost understudied in non-neuronal tissues, though previous studies on germline development during oogenesis may suggest a special function of this protein also in ovarian tissue. In addition, the well-documented association of FMR1 premutation state with fragile X-related premature ovarian insufficiency adds interest to the role of FMRP in ovarian physiology. The aim of the present work was to investigate the expression of Fmr1 mRNA and its protein, FMRP, at different stages of rat follicular development. By immunohistochemical studies we demonstrated FMRP expression in granulosa, theca and germ cells in all stages of follicular development. In addition, changes in Fmr1 expression, both at the protein and mRNA levels, were observed. FMRP levels increased upon follicular development while preantral and early antral follicles presented similar levels of Fmr1 transcripts with decreased expression in preovulatory follicles. These observations suggest that Fmr1 expression in the ovary is regulated at different and perhaps independent levels. In addition, our results show expression of at least four different isoforms of FMRP during all stages of follicular growth with expression patterns that differ from those observed in brain and testis. Our study shows a regulated expression of Fmr1, both at mRNA and protein levels, during rat follicular development.